Implementation of Competence-Based Approach as a Tool of Training Future Teachers in Higher Education - Zdanevych, Larysa (Pedagogical Discourse, 2015)
Analysis of different theoretical views to the problem of competence-based approach, as one of the instruments of professional training of the future pedagogues in higher educational establishment has been done in the article. It is mentioned that competence-based approach – is the approach to determine the results of teaching, based on their description in the terms of competences, and it is the key methodological instrument of realization of the aim of Bologna process. It is determined that competence-based approach means directivity of education to forming of the student competences, with the help of professional and social tasks in educational process. Competence-based approach expects rise of subjectivity of the student himself or herself in educational process, connected with the ability to orientate in the informational stream and reflection, that is behavioral models are formed, when the graduate is able not only to reproduct information (knowlegde), but to orientate independently in the situation, and qualified solve the tasks, which arise. It is found out that realization of competence-based approachis impossible without strengthening of practical directivity of professional educationunder the conditions of its fundamentality preserving. The categories «capacity», «competence» and «professional competence» are analyzed. It is determined that competence of the future tutor is studied as a separate kind of professional pedagogical competence in the sphere of pre-school education, which is closely connected with and mutually conditioned with other kinds of psychologic-pedagogical competence of the future tutors of this profile, and which is the result of mastering of a number of professional capacities, stipulated both by the specificity of work with children, and peculiarities of the process of social development of preschoolers.